The Effect Of Management Policies On Employee Performance At The Dairi Regency Agriculture, Food Security And Fisheries Office - Wandi Bron Ohto Tumanggor; Mesra B (Yayasan Multidimensi Kreatif, 2024)
The Purpose Of This Study Is To Analyze The Influence Of Management Policy On Employee Performance In The Department Of Agriculture, Food Security, And Fisheries Of Dairi Regency. This Study Uses A Causal Associative Quantitative Method With A Population Of 235 Employees, And The Sampling Technique Used Is Purposive Sampling Where Only Employees With Asn Status Totals 131 Employees. Data Was Obtained Through Questionnaires Distributed To Employees From Various Divisions. The Results Of The Study Show That Management Policy Has A Positive And Significant Effect On Employee Performance. This Is Evidenced By The T-Count Value Of 20.729 > 1.65675, And The Significance Value Of 0.000 < 0.05. A Regression Coefficient Of 1,723 Indicates That Every 1 Point Increase In Management Policy Style Will Lead To An Increase In Employee Performance By 1,723 Points, Assuming The Other Variables Remain. The Results Of The Determination Coefficient Test Showed An Adjusted R Square Value Of 0.767 Or 76.7%, Which Showed That Management Policy Had A Significant Influence On Employee Performance, And The Remaining 23.3% Was Influenced By Other Factors That Had Not Been Studied In This Study. Overall, This Study Concludes That Management Policy Style Can Contribute To Improving Employee Performance In The Department Of Agriculture, Food Security, And Fisheries Of Dairi Regency.